Pediatric cardiac arrest registries and survival outcomes: A European study - Markel, Franziska; Djakow, Jana; Biarent, Dominique; de Lucas, Nieves; Castillo, Jimena Del; Skellett, Sophie; Turner, Nigel M; Buysse, Corinne M P; Lauridsen, Kasper G (Resuscitation plus, 2025)
OBJECTIVE: The epidemiology of pediatric cardiac arrest in Europe is largely unknown. We aimed to characterize pediatric cardiac arrest registries and obtain the first survival outcome data on pediatric cardiac arrest in Europe. DESIGN: This is a prospective multinational survey. SETTING: We surveyed all 53 countries in Europe asking about: the existence registries for pediatric out-of-hospital cardiac arrest (pOHCA) and/or in-hospital cardiac arrest (pIHCA)), the data collected, and the structure of the registries. Subsequently, we investigated outcomes (number of pOHCA/pIHCA since start of the registry, return of spontaneous circulation (ROSC), survival to hospital discharge/30-day survival) from the countries with active registries. PATIENTS AND INTERVENTIONS: We obtained information from 33 countries including 25 of the 27 European Union states. MEASUREMENTS AND MAIN RESULTS: Thirteen countries (39%) have an ongoing pediatric cardiac arrest registry (pOHCA: 11 countries, pIHCA: 8 countries). All use the Utstein template for data collection. Five countries (15%) collect data about CPR quality. Eleven countries (33%) expressed interest in European collaboration on registry data. Overall, 13 countries reported data on outcomes from a total of 17,708 pOHCAs and 2,743 pIHCAs. The ROSC rate after pOHCA ranges from 10% to 72% as compared to 60% to 72% after pIHCA. Survival to hospital discharge ranges from 16% to 39% after pOHCA as compared to 32% to 57% after pIHCA. CONCLUSIONS: Less than 40% of the European countries have a pOHCA and/or pIHCA registry, reporting a wide variety in survival rates, especially after pOHCA. More systematic data collection is needed to identify the real incidence and outcomes from pediatric cardiac arrest, ideally through a joint European registry.
Keywords: Cardiac arrest registries; Outcomes; Pediatric cardiac arrest; Epidemiology